057 Age-related changes in sleep impact learning-related functional connectivity in the cortico-striatal-hippocampal system. (3rd May 2021) - Smith, Dylan; Fang, Zhuo; Carrier, Julie; Doyon, Julien; Fogel, Stuart
Abstract: Introduction: Older adults do not consolidate newly learned motor sequences with the same efficiency compared to younger adults, and there is evidence that enhanced consolidation by sleep is also impaired with age. It is known that brain activity in the hippocampal-cortical-striatal network is important for off-line consolidation of motor-sequences, however, the intricacies of how communication within this network is altered by sleep in order to facilitate consolidation is not known. Methods: In this study, 37 young and 49 older individuals underwent resting state MRI before training on a MSL task, as well as after training, and then once again, after either a nap or a period of awake rest. Results: Preliminary analysis showed a significant difference in functional communication (FC) in the hippocampal-cortical-striatal network, with younger subjects showing increased FC compared to younger individuals. Follow-up analyses revealed this effect was driven by younger subjects who showed an increase in FC between striatum and motor cortices, as well as older subjects who showed decreased FC between hippocampus, striatum, and precuneus. Therefore, an opposite effect of sleep was observed in younger vs. older participants, where young participants primarily showed increased communication in the striatal-motor network and older participants showed decrease in key nodes of the default mode network. Conclusion: This shows that changes to sleeps' ability to optimize functional communication may disrupt sleep-enhanced MSL consolidation in old age. Support (if any): Canadian Institutes of Health Research